Zuhud Milenial Dalam Perspektif Hadis - Endrika Widdia Putri (IAIN Bengkulu, 2019)
The age development made the concept of zuhud experience a shifting paradigm. In the beginning of its development, zuhud was understood which was ignoring the world and more concerned with the afterlife. Then, comes the new paradigm that the concept of zuhud is no longer distancing the world and is more likely to be hereafter. However, the zuhud that develops is transforming the values of divinity in daily life in order to create social piety, and balance between the life of the world and the hereafter. This is also called Millennial Zuhud. Millennial Zuhud requires that people not only have good relations with God (habblumminallah), but also good relations with humans (habblumminannas) and nature. Zuhud millennial is close to the world because humans live in the world and are close to God because this human purpose was created. Life of the world does not neglect closeness with God. The concept of zuhud like this can be seen in the hadith. The zuhud values contained in the hadith are tawazun (balance), social piety, patience, gratitude, and qanaah.